Effect of fire in seed banks of agroforestry systems, Pará, Brazil - Alvino-Rayol, Fabrízia de Oliveira; Rayol, Breno Pinto (Revista de Ciências Agroveterinárias, 2019)
The objective of this study was to evaluate the effect of fire on floristic composition, structure, and diversity of seed banks in different agroforestry systems (SAF). We evaluated four systems: SAF 1 - Schizolobium amazonicum and Vigna unguiculata using fire to prepare the plot; b) SAF 2 - Schizolobium amazonicum, Vigna unguiculata and Canavalia ensiformes without the use of fire; c) SAF 3 - Schizolobium amazonicum, Euterpe oleracea and Theobroma grandiflorum with the use of fire; com; d) SAF 4 - Schizolobium amazonicum, Euterpe oleraceae and Theobroma grandiflorum without the use of fire. The seed bank was determined from 20 soil samples from 50 x 50 cm at 0 - 5 cm depth level, totalizing 80 samples. For seed counting and identification, seedling emergence technique under greenhouse conditions was used. The most important species were Cyperus Laxus, Olyra glaberrima, and Myrciaria tenella. The seed banks of the agroforestry systems that were managed with fire were basically herbaceous species typical of agricultural lands and disturbed environments. Fire influenced the floristic, structure, diversity, and infestation of seed banks in agroforestry systems evaluated.